Використання web-технологій для автоматизації розробки технологічних карт вирощування сільськогосподарських культур - Лубко, Дмитро Вікторович; Lubko, Dmytro (Запоріжжя : 2022, 2022)
UA: Мета даної статті – розглянути методи використання web-технологій для автоматизації розробки технологічних карт вирощування сільськогосподарських культур. Розглянуто методи використання web-технологій для автоматизації розробки технологічних карт вирощування сільськогосподарських культур. Виконана робота вирішує одне з найважливіших питань для будь-якого фермера: дозволяє автоматизувати формування технологічних карт вирощування сільськогосподарських культур враховуючи технічні та технологічні показники свого господарства. Розробка такої автоматизованої web-системи значно спрощує роботу фермеру по розробці технологічних карт вирощування культур у господарстві. Це дозволить значно підвищити ефективність праці та зберегти робочий час аграрія. EN: The purpose of this article is to consider the methods of using web technologies to automate the development of technological maps of growing agricultural crops. The methods of using web technologies to automate the development of technological maps of growing agricultural crops are considered. The completed work solves one of the most important issues for any farmer: it allows you to automate the formation of technological maps for the cultivation of agricultural crops, taking into account the technical and technological indicators of your farm. The development of such an automated web system greatly simplifies the work of the farmer in developing technological maps of growing crops in the farm. This will significantly increase labor efficiency and preserve the farmer's working hours. The technological map is, first of all, a planning and normative document, which shows the culture cultivation technology, calculated planned labor costs and material and monetary costs, defined standards of costs per unit of area and unit of production of the culture being grown. On the basis of technological maps, a complex of agrotechnical and organizational and economic measures is carried out, which to the greatest extent correspond to the specific conditions of management: for each agricultural crop, the most economical machine-tractor units are assembled for each operation, labor costs, the amount of additional, increased and incentive wages are calculated, and as well as the general wage fund with accrual to social insurance. During the manual development of technological maps, there are problems with the correct selection of all factors, equipment, techniques, etc., therefore, its filling and structuring can cause significant difficulties. That is why we propose to consider methods of using web technologies to automate the process of developing technological maps of growing agricultural crops with the help of creating a special web resource (site).
Use of web technologies for automation of the development of technological maps of growing of agricultural crops
Лубко Д. В. Використання web-технологій для автоматизації розробки технологічних карт вирощування сільськогосподарських культур. Науковий вісник Таврійського державного агротехнологічного університету : електронне наукове фахове видання. 2022. Вип. 12. том 3. C. 356-363.
Keywords: web-технології; процес автоматизації; сільськогосподарські культури; вирощування; технологічні карти; web technologies; automation process; agricultural crops; cultivation; technological maps